Communication and punishment in voluntary contribution experiments - Olivier Bochet; Talbot Page; Louis Putterman (Brown University, Department of Economics, 2002)
We compare two devices previously found to increase contributions to public goods in laboratory experiments: communication, and punishment (allowing subjects to engage in costly reductions of one another's earnings after learning of their contribution decisions). We find that communication increases contributions more than punishment, and, taking into account the cost of punishment, only communication significantly increases subjects' earnings and thus efficiency. We study three forms of communication to understand what elements of communication are essential to this result: exchanges of nume rical messages, exchanges of verbal messages through a computer chat room, and face-to-face communication. Compared with a baseline of no communication and no punishment, we find that chat room communication increases cooperation and efficiency nearly as much as face-to-face communication, even though the chat room environment does not communicate cues of facial expression, tone of voice, and body language. Verbal communication is so effective that adding a punishment option to it does not significantly change the level of contributions or earnings. In contrast, communication limited to sending numerical messages has no net effect on contributions or efficiency.
Keywords: C91; H41; D23; 330; Public goods; collective action; communication; punishment; cheap talk; Öffentliches Gut; Kommunikation; Test; Theorie